Electrocatalytic Reduction of Carbon Dioxide on a Cobalt Tetrakis(4-Aminophenyl)Porphyrin Modified Electrode in bmimbf4 - Garcia-Morgado, M; Garcia-Morgado, M (Royal Society of Chemistry, 2014)
Electro-catalytic reduction of carbon dioxide has been studied with cobalt 5,10,15,20 tetrakis(4-aminophenyl)porphyrin forming a conducting polymer on an indium tin oxide electrode, using an ionic liquid as a novel reaction media. Electrocatalytic reduction of CO2 has been carried out, the potential at which this occurs has been reduced from -2.4 V vs. Ag/AgCl reported before, to -0.8 V vs. Ag/AgCl which means a significant energy gain regarding the electrochemical fixation of CO2. Electrochemical impedance spectroscopy (EIS) experiments have been carried out in order to understand the electrical behavior of the modified electrode in ionic liquid medium. Spectroelectrochemical evidence suggests that the reactive species which promotes the reaction is an electrochemically generated Co(i) porphyrin species which can be detected in an inert atmosphere but not in the carbon dioxide saturated medium. © 2014 the Partner Organisations.